A simple technique for the management of refractory gastrostomy site complications a technical innovation in gastrostomy tube site revision - Rebecca M. Rentea; Wendy J. Svetanoff; Charlene Dekonenko; Courtney Pisano; Charles L. Snyder (Elsevier, 2020)
Introduction: Longstanding gastrostomy sites are prone to leakage and excoriation secondary to protrusion of gastric mucosa into the tract, dilation of the site over time, and development of refractory granulation tissue. Surgical revision with creation of a new gastric and skin exit site can be difficult. We describe a technique to re-site a gastrostomy tube (GT) utilizing the existing GT site. Materials and methods: For one patient with gastrostomy site refractory complications, we re-sited the GT using the existing site. A clamp was placed through the old GT site and was palpated through the abdominal wall. An incision over the tip was made and a silk tie was passed from this new site, exiting through the old site. A One-step™ device was then pulled from the old site out through the new site, and closure of the old gastrostomy was performed. Results: The procedure took approximately 40 min to complete. Oral and GT intake was started within 3 hours. There were no intra- or post-operative complications. The patient was discharged home the same day. Conclusion: This simple technique allows for revision of a gastrostomy tube without the use of laparoscopy and permits a cosmetically pleasing incision. Keywords: Gastrostomy tube, Gastrostomy site revision, Revision